2008
DOI: 10.1002/dat.20275
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Hemodialysis Patients in Area of High Incidence of Mycobacterium tuberculosis and Human Immunodeficiency Virus Infection

Abstract: BACKGROUND Hemodialysis (HD) patients have an increased incidence of tuberculosis (TB), which may be due to decreased cellular immunity, the presence of malnutrition, and the use of immunosuppressive drugs. Poor living conditions, overcrowding, and human immunodeficiency virus (HIV) infection could be considered added risk factors. This study analyzed the incidence and clinical characteristics of TB among HD patients in an area where TB and HIV infection have a high prevalence. METHODS In this multicenter stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(18 reference statements)
3
3
1
Order By: Relevance
“…In our series, the prevalence of TB was 56.2 times higher than in the Senegalese general population where it is estimated to be 200/100,000. The high prevalence of TB in the CHD patients compared to the general population was confirmed by other authors [3] [7] [10] [11] [15]. A literature review reported that the incidence is 6.9 to 52.5 times higher in dialysis patients [16].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…In our series, the prevalence of TB was 56.2 times higher than in the Senegalese general population where it is estimated to be 200/100,000. The high prevalence of TB in the CHD patients compared to the general population was confirmed by other authors [3] [7] [10] [11] [15]. A literature review reported that the incidence is 6.9 to 52.5 times higher in dialysis patients [16].…”
Section: Discussionsupporting
confidence: 56%
“…In addition to the poor specificity of symptoms, also the site of TB is often extra-pulmonary. In the literature, this frequency varies from 47% to 100%; the lymph node and peritoneal tuberculosis are the most common sites [3] [5] [9] [11] [15]. In our study, the extrapulmonary location was predominant (79%).…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations